Competitiveness, labor market institutions, and monetary policy - Ester Faia (IZA World of Labor, 2017)
In the presence of rigid prices, movements in the exchange rate help to absorb external shocks and to reduce changes in net exports. However, they also affect firms' competitiveness, marginal costs, and labor demand. In countries where labor market institutions hinder wage adjustment (for example due to high union density or more rigid collective bargaining agreements), firms are less competitive: labor demand is then more sensitive to external shocks, increasing the risk of unemployment.
Keywords: J3; F66; 330; competitiveness; wage adjustment; labor market institutions; real exchange rate; monetary policy